Investigation of the Copper Gettering Mechanism of Oxide Precipitates in Silicon. (1st January 2015) - Kissinger, G.; Kot, D.; Klingsporn, M.; Schubert, M. A.; Sattler, A.; Müller, T.
Abstract : One of the reasons why the principal gettering mechanism of copper at oxide precipitates is not yet clarified is that it was not possible to identify the presence and measure the copper concentration in the vicinity of oxide precipitates. To overcome the problem we used a 14.5 nm thick thermal oxide layer as a model system for an oxide precipitate to localize the place where the copper is collected. We also analyzed a plate-like oxide precipitate by EDX and EELS and compared the results with the analysis carried out on the oxide layer. It is demonstrated that both the interface between the oxide precipitate being SiO2 and the silicon matrix and the interface between the thermal oxide and silicon consist of a 2–3 nm thick SiO layer. As the results of these experiments also show that copper segregates at the SiO interface layer of the thermal oxide it is concluded that gettering of copper by oxide precipitates is based on segregation of copper to the SiO interface layer.